12-6x=3(4-2x)

Simple and best practice solution for 12-6x=3(4-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-6x=3(4-2x) equation:



12-6x=3(4-2x)
We move all terms to the left:
12-6x-(3(4-2x))=0
We add all the numbers together, and all the variables
-6x-(3(-2x+4))+12=0
We calculate terms in parentheses: -(3(-2x+4)), so:
3(-2x+4)
We multiply parentheses
-6x+12
Back to the equation:
-(-6x+12)
We get rid of parentheses
-6x+6x-12+12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2x+21=8x=27 | | .75x-4=-85x+1 | | 8x-5x-2=0 | | -10n+5-3=83 | | 3b/8=21/8 | | -5(4x-3)=-85 | | 2x-x=2x+x-108 | | 12w-41=3 | | 10z-z=-1+4z-1-3 | | 1/5*k=288 | | 1/5k=288 | | -5-2n-5n=9 | | 3q−13=–6q+13+11q | | x^+37=118 | | 18n=20+20n | | .)3(2x-1)+5=14* | | –8g+13=–7g+7 | | |4x+4|=20 | | 7x-(-10x)-8x= | | 5x+3(-x+11)=3 | | 0=-(x-7)^2+3(x+2)-3x | | 5.5y+3.5=5y-5 | | 4x4-7x2=0 | | 1/2=b/8 | | 13+4y=81 | | 2u2+2u2= | | p+6=52 | | X+0.25x=79.00 | | 2r²-5r-12=0 | | x²=1/100 | | 7÷2x=4+1÷2x | | 1+x-1+12x=12x-3 |

Equations solver categories